Identification of Olea europaea CBF/DREB1 Family Genes in Abnormal Temperature Stress Response - Guanghui Hai; Sisi Chen; Muhong Xie; Chenhao Li; Qian Wang; Ying Lu; Yan Tang; Zhengwu Zhang; Guiyan Yang (Agronomy)
Olea europaea, native to the Mediterranean region, has been widely cultivated for the nutritional content of its fruits and leaves. To adapt to climates beyond the Mediterranean, research on the climatic adaptation of O. europaea is urgently needed. Therefore, in this study, the CBF/DREB1 family genes in olives, which are related to cold tolerance, were genome-wide characterized. In total, four OeCBFs were screened; their open reading frame (ORF) were 552~684 bp in length, the encoded proteins were 20,786.60~25,235.16 Da, with 183~227 amino acids, and the theoretical isoelectric point (pI) were 4.91~9.13. The transcription of four OeCBFs was significantly different in olive tissues, especially OeCBF2 and OeCBF4, which were substantially more highly-expressed in aboveground tissues (terminal buds, young leaves, old leaves, and stems) than in underground tissues (thick and fine roots). Exposed to cold stress, OeCBF2 and OeCBF4 were up-regulated more obviously in olive leaves and stems, while OeCBF3 was induced to higher levels in the roots, implying the adaptation potential of the OeCBFs to low temperature stress. A comparison of the expression of the four OeCBFs in two varieties, Picholine (more tolerant to the other one) and Arbequina, found that the expression of OeCBFs was higher in most tissues of Picholine than that of Arbequina. When exposed to cold stress, the expression of the OeCBFs was also higher in the leaves and roots of Picholine than in Arbequina, further confirming the correlation between OeCBFs and cold tolerance of olive trees. This study not only deepens our understanding of the CBF gene family in olives, but also provides significant genetic information for olive breeding and improvement.